Bulk graphdiyne powder applied for highly efficient lithium storage. Issue 10 (18th December 2014) - Zhang, Shengliang; Liu, Huibiao; Huang, Changshui; Cui, Guanglei; Li, Yuliang
Abstract : Bulk graphdiyne powder with porous structure was synthesized and applied for highly efficient lithium storage, exhibiting excellent electrochemical performance. Abstract : Here, we prepared bulk graphdiyne (GDY) powder with porous structure and explored its lithium storage properties. The assembled lithium ion batteries exhibited superior electrochemical performance, including high specific capacity, excellent rate performance and long cycle life, which should be attributed to the unique structure, high electronic conductivity and chemical stability of GDY.